The evaluation of the retinal findings in the fundoscopic examination of the preeclampsia patients - Kalaycı, Mustafa; Şahin, Özgür (Perinatal Medicine Foundation, 2020)
Objective We aimed to evaluate and compare the retinal findings of the fundoscopic examination of mild and severe preeclampsia cases in our study. Methods The data of 165 patients who admitted to Somalia Mogadishu-Turkey Training and Research Hospital, were hospitalized in the obstetrics and gynecology clinic upon the preeclampsia diagnoses and for whom the eye consultation was requested between January 2017 and January 2020 were evaluated retrospectively. The patients were grouped according to their age, week of gestation, delivery type (cesarean section - normal delivery) and preeclampsia severity (mild - severe). The patients found to have hypertensive retinopathy changes on right or left eye or both eyes were recorded as positive in terms of the findings. Results While no pathological finding was observed in 104 (63.1%) of 165 patients who underwent fundoscopic examination, 61 (36.9%) patients had retinal pathology. Of the patients found to have pathology in their fundoscopic findings, 39 (63.9%) were severely preeclamptic and 22 (36.1%) were mildly preeclamptic. The pregnancy of 51 (83.6%) of these 61 patients was terminated at preterm period (<37 weeks of gestation) and of 10 (16.4) at term (≥37 weeks of gestation). Of 61 patients found to have retinal pathology, 36 (59%) had hypertensive retinopathy, 9 (14.8%) had macular edema, 6 (9.8%) had hypertensive hemorrhage, 4 (6.6%) had pigment epithelial detachment, 2 (3.3%) had bilateral retinal detachment, 2 (3.3%) had left retinal detachment, and 2 (3.3%) had edema in bilateral optical disk. Conclusion While visual complaints are very common in preeclamptic pregnant women, rare but serious complications such retinal detachment, pigment epithelial detachment, macular edema and papilledema as may also develop. Other retinal diseases in addition to hypertensive retinopathy should also be considered during the fundoscopic examination of preeclamptic pregnant women. The clinicians should be aware of these ocular indications and they should work in cooperation to prevent blindness during or after pregnancy. It seems that terminating the pregnancy in preeclamptic pregnant women who develop visual impairment is effective to regain visual capability.